Experimental study and system analysis of finding the best inorganics additive to enhance quality of Malaysian engine oil / Azmi Roslan - Roslan, Azmi (2013)
This study performed a system analysis for specifying the best inorganic metals in engine oil by evaluating its ability on behavior of the system. Inorganic metals is one of the additives in engine oil and this research realized on the difficulty in specifying it’s optimum concentration since the types and concentration of that elements did not disclosed by marketers to the public due to their important and highly details. Five different samples were prepared and tested on purpose of understanding on its types and concentration, heat capacity, viscosity behavior, kinematic viscosity and viscosity index. Evaluation of inorganic metal concentration was assessed by Inductively Coupled Plasma Optical Spectrometer. Samples viscosity was obtained using rotational viscometer. Tests were made under constant shear rate of 600 s'1 and temperature setting from 40 to 100°C. By collecting the information of the samples viscosity, determination of the best engine oil was carried out by measuring area under the curve for each of samples graph. Heat capacity for each samples were determined using bomb calorimeter in adiabatic mode of operation. Kinematic viscosities of engine oils were assessed using VH2 Viscometer Houillion at 40 and 100°C and viscosity index was calculated according to ASTM D2270 method. System analysis performed found that, the quality of Malaysian engine oil increased by increasing the concentration of elements by; Ferrum = 0.04-0.05 ppm, Arsenic = 0.1 ppm, Cobalt = 1.3-1.4 ppm, Cuprum I = 0.3-0.4 ppm, Cuprum II = 0.3-0.4 ppm, Nickel = 0.04-0.05 ppm, Cadmium = 0.1 ppm and Titanium =0.03-0.04 ppm. In addition, an attempted of adding Aluminum oxide had also been made. A set of experiment (heat capacity, viscosity behavior and kinematic viscosity) to validate system identification was carried out and it was found that; Titanium, Copper, Cadmium, and Arsenic had a big effect in increasing the quality of Malaysian engine oil, whereas, Nickel, Cobalt and Aluminum does not.